Duszpasterstwo Akademickie w koncepcji wspólnoty ochronnej B. Newmana - Błasiak, Dominika (Śląskie Studia Historyczno-Teologiczne, 2006)
The author of the following dissertation verifies statements of B. Newman’s concept of protective community confronting it with specific centers of Diocesan Catholic Youth Conference. Among others those statements are: 1. The protective community gives its members an opportunity of escaping from wider social structures. 2. The protective community has exclusive character. To conclude, the specific centers of DCYC can act as protective community for some of its members, but DCYC cannot be considered as an example of a typical protective community. The specific centers of DCYC are rather category of participation community created by V. Pons.